Teaching Yes, And … Improv in Sales Classes: Enhancing Student Adaptive Selling Skills, Sales Performance, and Teaching Evaluations. (August 2014) - Rocco, Richard A.; Whalen, D. Joel
In an application of experiential learning, assessment, and career development, this article reports a field experiment of teaching sales students adaptive selling skills via an Improvisational (Improv) Comedy technique: Yes, And . Students learn this well-established theatrical improv method via classroom lecture, demonstration, and role-playing exercises. A control group (no improv training) experienced all aspects of the class with the exception of the improv training. After the classroom instruction, both student groups (improv and no -improv trained) participated in a real-world, 4-week sales project selling tickets for professional sport teams that partner with the class. The study's findings reveal increased ticket sales performance among the improv group students who learn Yes, And . Also students in the improv group gave higher class evaluations. Methods presented in this article could be utilized as an in-class exercise or as an integral part of a semester-long sales project.